Looking for the paths of the cooperative and solidarity sector - Rodríguez Espinosa , Néstor Alfonso; Dávila Ladrón de Guevara, Miguel Ricardo (Cooperativismo & Desarrollo, 2020)
This article aims to identify where the current dynamics of the cooperative and solidarity sector is located. To achieve this objective, experts are consulted on the scenario in which this sector is currently transiting, reviewing the fulfillment or not of the strategic objectives set out in the work entitled “Application of the strategic prospective model to the Colombian cooperative sector. Horizon: year 2031 ”published in 2014 by the Institute of Studies of the Public Ministry. Similarly, evidence was sought in documents published by state agencies and the sector itself. The main finding of this work is related to the location of the sector in a similar state to that of five years ago, with some important advances, but not enough to consider transformations that lead to different scenarios of greater incidence in the life of the regions in which it develops. The foregoing leads us to conclude that if this state of affairs in the sector continues, its development will be influenced by the force of external dynamics, either from social movements or the instrumentalization of the current rulers, as has been observed. historically.